2022
DOI: 10.30541/v51i4iipp.381-396
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fiscal Policy in Human Development: The Pakistan’s Perspective

Abstract: Human development considered as the engine of the economic growth as it improves the economy’s strength and increases the standard of living of the people, increases the choices and maximises the welfare of the society that is the prime objective of any government. The development of the human capabilities is also necessary for the sustainable growth, as there are many channels through which human development foster the economic growth. It increases the labour producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
2
11
0
1
Order By: Relevance
“…He found that government consumption spending effected the human development in a positive manner. Ali et al (2012) make a study about impacts of government expenditures and democracy on human development. According to the results of the study, while an increase in income per capita and education spending has positive effects on human development, current expenditures have negative effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…He found that government consumption spending effected the human development in a positive manner. Ali et al (2012) make a study about impacts of government expenditures and democracy on human development. According to the results of the study, while an increase in income per capita and education spending has positive effects on human development, current expenditures have negative effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, this phenomenon is also seen in Pakistan. His research (Ali et al, 2012) revealed a phenomenon of an increase in per capita income and education expenditure which has a positive effect. Current spending has a negative impact on human development.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the argument that the effectiveness of government spending on welfare is dependent on sectoral and component of the spending (Anderson et al 2018). After applying an ARDL estimation technique, Ali et al (2012) established that both government development expenditure and education expenditure have significant positive effects on HDI in Pakistan, whereas recurrent expenditure had negative and insignificant impact.…”
Section: Brief Review Of Relevant Literaturementioning
confidence: 99%